Penerapan Model Pembelajaran ICM dalam Meningkatkan Aktivitas Belajar dan Pemahaman Konsep Penjumlahan dan Pengurangan Bilangan - Mutia Oktiani mutia; Oktian Fajar Nugroho (Program Studi Pendidikan Guru Sekolah Dasar, Universitas Muhammadiyah Sukabumi, 2020)
This research was conducted in class III public elementary school 2 Pasirkembang with a total of 28 students in the even semester of the 2019/2020 academic year. The procedure in this study went through two cycles, where each cycle consisted of; (1) the planning stage, (2) the implementation phase of the action, (3) the observation phase, (4) the reflection pahse. Collecting data in this study using observation sheets of student learning activities, observation aheets of teacher activities in using the index card match learning model, test questions to measure students’ understanding of concepts in the material addition and subtraction of numbers, and use aquestionnaire to determine student responses to the learning model index card match. Data analysis techniques in this research are qualitative and quantitative analysis. The results showed that the application of numbers in class III public elementary school 2 Pasirkembang could increase learning activities and concept understanding. This reults can be seen from the average value of cycle I activity (61%), in cycle II (88%) and an increase of (27%). Average learning outcomes of students’ understanding of concepts in the material addition and subtraction of numbers in the first cycle (64%), in the second (92%).